Analysis of the range of oat-based products - Rudnyk, Anna; Khvorost, Olha; Skrebtsova, Kateryna; Fedchenkova, Yuliia (Annals of Mechnikov's Institute, 2025)
Introduction. The use of cultivated food crops as sources of medicinal raw materials is promising. Popular varieties cultivated in Ukraine are oat (Avena sativa L.) varieties Salomon, Neptune and Chernihivsky 28. Raw materials for the creation of medicines, dietary supplements, cosmetic and food products are grass of milky-wax ripeness, straw, grain and sprouts. There is data on antioxidant, anti-inflammatory, immunomodulatory, hypoglycemic, gastroprotective, hypolipidemic, cardioprotective, psychotropic effects, positive effect on cognitive brain functions. The presence of a wide raw material base, significant use in the food industry, diverse chemical composition, pharmacological activity, oat raw materials as a source of BAS require more in-depth research. The study of oat products on the Ukrainian market is expedient and relevant in this aspect. The purpose of the work. To determine the prospects for developing a medicinal product based on oat seed raw materials, outlining specific steps in the process of obtaining an API. Material and methods. Sources of scientific information (Google Scholar, Pubmed), online trading platforms (EVA, Rozetka, Prom.ua, OLX.ua), content analysis with subsequent data systematization and market segmentation. Results and discussion. As part of our research into the Ukrainian market, we identified approximately 100 oat-based products and analyzed their range by producer country. Currently, there are at least 15 countries producing oat-based products on the Ukrainian market. The lion's share is made up of domestic producers (41%). Moreover, most of the products are dietary supplements. Conclusions. The results of the study indicate that the domestic market of herbal remedies based on oats is represented by a fairly wide range. It should be noted that it is not import-dependent, since the vast majority of the nomenclature consists of remedies of domestic origin. Given the popularity of the use of oats as a source of BAS, the availability of raw materials, powerful chemical composition, and confirmed therapeutic effect, the development of domestic original monopreparations and complex medicines based on oat grass of waxy-milk ripeness is relevant.